PERANCANGAN JOURNALING BOOK BERTEMA SELF-LOVE UNTUK GEN Z (STUDI KASUS: PEREMPUAN KELAHIRAN 1997-2012): DESIGN OF SELF-LOVE THEMED JOURNALING BOOKS FOR GEN Z (CASE STUDY: WOMEN BORN IN 1997-2012) - Annisa Dinar Azahra; Elda Franzia Jasjfi; Agung Eko Budiwaspada (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2025)
Design of Self-Love Themed Journaling Books for Gen Z (Case Study: Women Born In 1997-2012). Gen Z faces a high level of competition in various aspects of their lives, including in education, career, and social. This high level of competition can cause insecurity among Gen Z, one of which is the feeling of insecurity. It is important for people to have boundaries in the way of loving themselves and being grateful for what they have right now. Self-Love is a state of self-appreciation. Journaling is a simple way to improve mental health. Illustration is the highest element as an attraction in the design of a book. Therefore, this study aims to produce a design concept and a journaling book with the theme of Self-Love for Gen Z. The type of research used is a qualitative approach. The data sources used by the researcher are primary and secondary data. The data obtained was collected by the following methods: observation, interviews, documentation, literature studies, and questionnaires. The method for data analysis in this study uses a qualitative data analysis method. After being analyzed, the validity of the data was carried out. The design method in this study uses the design thinking method, namely: Emphatize, Define, Ideate, Prototype, and Test. The design concept generated for this self-love-themed journaling book is "10 Minutes Journaling" with 4 stages of Self-Love. The result of this research is to produce a journaling book with the theme of Self-Love for Gen Z.